2021
DOI: 10.1111/pai.13484
|View full text |Cite
|
Sign up to set email alerts
|

Omalizumab outcomes for up to 6 years in pediatric patients with severe persistent allergic asthma

Abstract: Background Various studies have assessed omalizumab outcomes in the clinical practice setting but follow‐up and/or number of patients included were limited. We aim to describe the long‐term outcomes of pediatric patients with severe persistent allergic asthma receiving omalizumab in the largest real‐life cohort reported to date. Methods ANCHORS was a multicenter, observational, retrospective cohort study conducted in 25 Pediatric Allergy and Pulmonology units in Spain. We collected data of patients < 18 years … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(39 citation statements)
references
References 26 publications
3
36
0
Order By: Relevance
“…In our study group, we observed a slight decrease in the mean counts of absolute eosinophil cells after one year of treatment. The effect seems to be correlated with the duration of treatment, the lowest value compared to baseline was recently reported in a study after 6 years of treatment [36]. The pulmonary function evaluated by both large (FEV1) and small (MEF50) airway functional parameters, improved over one year of treatment with Omalizumab.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…In our study group, we observed a slight decrease in the mean counts of absolute eosinophil cells after one year of treatment. The effect seems to be correlated with the duration of treatment, the lowest value compared to baseline was recently reported in a study after 6 years of treatment [36]. The pulmonary function evaluated by both large (FEV1) and small (MEF50) airway functional parameters, improved over one year of treatment with Omalizumab.…”
Section: Discussionmentioning
confidence: 77%
“…Three pivotal Phase III clinical trials in patients with moderate-to-severe asthma were performed in the USA and Europe on a population of 1071 ICS-dependent symptomatic adolescents and adults, and 334 pediatric patients (aged 6-12 years), followed by other 25 trials, enrolling a total of 6382 patients with uncontrolled allergic asthma analysed a Cochrane meta-analysis, resulted all in effective reduction of asthma exacerbations by omalizumab treatment [32][33]. Recent systematic reviews of the results of multiple randomized, blinded, placebo-controlled phase III studies involving children 6 to 11 years of age [34] or adults and children over 6 years old age [35,36] resulted also in effective improvement in asthma control by reducing asthma exacerbations, hospital admissions, acute asthma attacks and the related need of oral corticosteroid (OCS) in severe asthmatic children. In our study, we observed a statistically significant reduction of the rate of exacerbations after the first year of treatment (mean rate of severe exacerbations decreased from 4.1 (2.8 SD) per patient during the previous year to 1.15 (0.78 SD) during the first year of treatment (p<0.0001)) and decrease of number of patients who developed asthma exacerbation, with less asthma acute symptoms induced by exercise (2 from 12 patients) and no exacerbations induced by viral respiratory infections during the first year of treatment with Omalizumab.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Three pivotal Phase III clinical trials in patients with moderate to severe asthma were performed in the USA and Europe on a population of 1071 ICS-dependent symptomatic adolescents and adults, and 334 children (aged 6–12 years), followed by 25 trials enrolling a total of 6382 patients with uncontrolled allergic asthma, were analyzed in a Cochrane meta-analysis, which demonstrated effective reduction of asthma exacerbations by Omalizumab treatment [ 31 , 32 ]. Recent systematic reviews of the results of multiple randomized, blinded, placebo-controlled phase III studies involving children aged 6 to 11 years [ 33 ] or adults and children aged over 6 years [ 33 , 34 ] also confirmed effective improvement in asthma control by Omalizumab, with reduction in asthma exacerbations, hospital admissions, acute asthma attacks and the related need for oral corticosteroid (OCS) in children with severe asthma. In our study, a statistically significant reduction in the rate of exacerbations during the first year of treatment was observed; the mean rate of severe exacerbations decreased from 4.1 ± 2.8 per patient during the previous year to 1.15 ± 0.78 during the first year of treatment ( p < 0.0001), and there was a decrease in the number of patients who developed asthma exacerbation, with less acute asthma symptoms induced by exercise (2 out 12 patients) and no exacerbations induced by viral respiratory infections during the first year of treatment with Omalizumab.…”
Section: Discussionmentioning
confidence: 99%
“…It is also important to note that the degree of decrease in the exacerbation rate has been correlated in clinical trials with the number of exacerbations before starting the treatment with Omalizumab, baseline PFTs, and eosinophil count, with different results in different studies, but with improvements being greater in children with more severe subtypes [ 38 ]. A raised absolute eosinophil count in peripheral blood is associated with a higher risk of asthma exacerbations [ 1 , 33 ]. In our study, 91.7% of the patients were polysensitized, a trait that, together with the high eosinophil counts and the increased and high levels of total IgE, are parameters related to the severity of asthma.…”
Section: Discussionmentioning
confidence: 99%